2008
DOI: 10.1029/2008gc002103
|View full text |Cite
|
Sign up to set email alerts
|

A model for the production of sulfur floc and “snowblower” events at mid‐ocean ridges

Abstract: [1] At mid-ocean ridges following magmatic eruptions, biogenic floc emerges from the seafloor and blankets regions of the seafloor in what have been called ''snowblower'' events. The floc often consists of filaments of elemental sulfur, and similar byproducts have been produced by hydrogen sulfide oxidizing bacteria in the laboratory. In this paper we estimate the rate of sulfur floc production in two ways. First, we compare the flux of H 2 S from high temperature vents and adjacent diffuse flow near 9°50 0 N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…At Axial snowblower vents, the Methanococci and other thermophiles are likely present due to flushing, while the Sulfurovum and Sulfurimonas are likely residents of shallower subsurface layers and experiencing a secondary bloom just below the seafloor. Modeling of the biogenic production of white floc after the 1991 eruption at 9°N East Pacific Rise suggested that the source of material for snowblower vents may be a combination of microbial bloom and a flushing of accumulated floc within the seafloor (Crowell et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…At Axial snowblower vents, the Methanococci and other thermophiles are likely present due to flushing, while the Sulfurovum and Sulfurimonas are likely residents of shallower subsurface layers and experiencing a secondary bloom just below the seafloor. Modeling of the biogenic production of white floc after the 1991 eruption at 9°N East Pacific Rise suggested that the source of material for snowblower vents may be a combination of microbial bloom and a flushing of accumulated floc within the seafloor (Crowell et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…However, recent rRNA gene surveys show that SUP05 are also widely distributed in pelagic environments, raising the question of whether the connection between plumes and subsurface is physical (i.e., transport only) or ecological (i.e., actively operating in similar niches in both environments) in nature. An extreme example of the physical transport of seafloor and/or subsurface material to the water column is “snowblower” vents that discharge elemental sulfur and bacterial filaments (Haymon et al, 1993; Crowell et al, 2008). Thermophilic microbes derived from the subsurface have also been observed in eruptive event plumes (Summit and Baross, 1998).…”
Section: Microbial Communities In Deep-sea Hydrothermal Plumesmentioning
confidence: 99%
“…additional energy and biomass enter vent food webs through photosynthetic organics and detritus, chemosynthetic organics and detritus, and abiotic organics. (Taylor and Wirsen, 1997;Huber et al, 2003;Crowell et al, 2008). Immediately following an eruption, the microbial biomass and sulfur floc is expelled in a "bloom" of productivity (Haymon et al, 1993;Tunnicliffe et al, 1997).…”
Section: Food Web Structurementioning
confidence: 99%